New Heterodinuclear Zn/Ln (Ln = Gd, Tb, Er, Yb) Complexes of Hexadentate N,N'-Bis(3-alkoxy-2-hydroxybenzyl)cyclohexane-1,2-diamines: Synthesis and Structure* - Kelly, Norman; Schnaars, Kathleen; Gloe, Kerstin; Doert, Thomas; Weigand, Jan J.; Gloe, Karsten (Australian Journal of Chemistry)
Two N,N'-bis(3-alkoxy-2-hydroxybenzyl)cyclohexane-1,2-diamine proligands, H2L1 (R = OCH3) and H2L2 (R = OC2H5), and five heterodinuclear ZnII/LnIII complexes, [Zn(L)(µ-CH3COO)Ln(NO3)2], containing [L1]2– and Gd3+, Tb3+, Er3+, or Yb3+ and [L2]2– and Yb3+ have been synthesised and structurally characterised. The complexes are isostructural and crystallise in the P21/n monoclinic space group. Zinc(ii) is coordinated by the inner N2O2 donor set of the ligand and an oxygen of the bridging acetate anion; the lanthanide(iii) ions possess an O9 coordination environment involving the interaction with the ligand’s outer O4 donor set, two bidentate nitrate ions, and the bridging acetate.

The enzyme-mediated autodeposition of casein: effect of enzyme immobilization on deposition of protein structures - Ruediger, Arne A.; Bremser, Wolfgang; Strube, Oliver I. (Journal of Coatings Technology and Research)

Nanoscaled Biocoatings via Enzyme Mediated Autodeposition of Casein - Ruediger, Arne A.; Bremser, Wolfgang; Strube, Oliver I. (Macromolecular Materials and Engineering)

Influences on the film thickness in the enzymatic autodeposition process of casein - Ruediger, Arne A.; Terborg, Elke; Bremser, Wolfgang; Strube, Oliver I. (Progress in Organic Coatings)

Enzyme-Mediated In Situ Synthesis and Deposition of Nonaggregated Melanin Protoparticles - Strube, Oliver I.; Büngeler, Anne; Bremser, Wolfgang (Macromolecular Materials and Engineering)

Influence of the Surface and Heat Treatment on the Bond Strength of Galvanized Steel/Aluminum Composites Joined by Plastic Deformation - Hoppe, Christian; Ebbert, Christoph; Grothe, Richard; Schmidt, Hans Christian; Hordych, Illia; Homberg, Werner; Maier, Hans Juergen; Grundmeier, Guido (ADVANCED ENGINEERING MATERIALS)
The influence of a chemical or mechanical surface modification followed by different post-heat treatments on the bond strength of galvanized steel/ aluminum composites is studied. An incremental rolling process is used for joint formation based on plastic deformation. The morphology, the chemical state of the modified surfaces as well as the cross-section, and local potential distribution of the welded zone is characterized by different microscopic and spectroscopic methods. The stability of the joint is analyzed by a shear-force test in combination with microscopic failure analysis. A clear correlation between pre/post-treatment and the joint strength is observed.

Molecular Engineering of Aluminum-Copper Interfaces for Joining by Plastic Deformation - Hoppe, Christian; Ebbert, Christoph; Voigt, Markus; Schmidt, Hans Christian; Rodman, Dmytro; Homberg, Werner; Maier, Hans Juergen; Grundmeier, Guido (ADVANCED ENGINEERING MATERIALS)
Interface modification based on ultra-thin mercapto-propyl(trimethoxy) silane (MPTMS) films is shown to promote joining of copper and aluminum by plastic deformation followed by a heat treatment. The surface morphology and the surface chemistry of the metal substrates were analyzed by means of FE-SEM, XPS, and FT-IRRAS. The spectroscopic data show that the MPTMS film is crosslinked via Si-O-Si bonds and that stable Cu-S and Si-O-Al interfacial bonds are formed. The shear-force tests of the joints led to force displacement curves that are characteristic for a covalently bonded interface. Complementary cross sectional SEM and EDS analysis of the joint proved that a defect-free interface was formed without any measureable interdiffusion of metals across the interface or cracking of an oxide films.

Nanoscale Structure of the Oil-Water Interface - Fukuto, M.; Ocko, B. M.; Bonthuis, D. J.; Netz, R. R.; Steinrück, Hans-Georg; Pontoni, D.; Kuzmenko, I.; Haddad, J.; Deutsch, M. (Physical Review Letters)

In Situ Study of Silicon Electrode Lithiation with X-ray Reflectivity - Cao, Chuntian; Steinrück, Hans-Georg; Shyam, Badri; Stone, Kevin H.; Toney, Michael F. (Nano Letters)

Self-Assembly, Dynamics, and Polymorphism of hIAPP(20–29) Aggregates at Solid–Liquid Interfaces - Hajiraissi, Roozbeh; Giner, Ignacio; Grundmeier, Guido; Keller, Adrian (Langmuir)

Regular Nanoscale Protein Patterns via Directed Adsorption through Self-Assembled DNA Origami Masks - Ramakrishnan, Saminathan; Subramaniam, Sivaraman; Stewart, A. Francis; Grundmeier, Guido; Keller, Adrian (ACS Applied Materials & Interfaces)

Temperature-Dependent Charge Transport through Individually Contacted DNA Origami-Based Au Nanowires. - Teschome, B; Facsko, S; Schönherr, T; Kerbusch, J; Keller, Adrian; Erbe, A (Langmuir)

DNA annealing by Redβ is insufficient for homologous recombination and the additional requirements involve intra- and inter-molecular interactions. - Subramaniam, S; Erler, A; Fu, J; Kranz, A; Tang, J; Gopalswamy, M; Ramakrishnan, S; Keller, Adrian; Grundmeier, Guido; Müller, D; Sattler, M; Stewart, AF (Scientific Reports)

Plasma-Enhanced Chemical Vapor Deposition (PE-CVD) yields better Hydrolytical Stability of Biocompatible SiOx Thin Films on Implant Alumina Ceramics compared to Rapid Thermal Evaporation Physical Vapor Deposition (PVD) - Böke, Frederik; Giner, Ignacio; Keller, Adrian; Grundmeier, Guido; Fischer, Horst (ACS Applied Materials & Interfaces)

Anisotropic metal growth on phospholipid nanodiscs via lipid bilayer expansion - Oertel, Jana; Keller, Adrian; Prinz, Julia; Schreiber, Benjamin; Hübner, René; Kerbusch, Jochen; Bald, Ilko; Fahmy, Karim (Scientific Reports)

Structural stability of DNA origami nanostructures in the presence of chaotropic agents - Ramakrishnan, Saminathan; Krainer, Georg; Grundmeier, Guido; Schlierf, Michael; Keller, Adrian (Nanoscale)

Adsorption and adhesion studies of PdSn-nanoparticles on protonated amine and carboxylic acid-terminated surfaces - Mosebach, Bastian; Bayer, Frank Markus; Fels, Carl-Christian; Voigt, Markus; Oezkaya, Berkem; Pomorska, Agata; Torun, Boray; Keller, Adrian; Grundmeier, Guido (Surface and Interface Analysis)

The Thermal Oxidation of TiAlN High Power Pulsed Magnetron Sputtering Hard Coatings as Revealed by Combined Ion and Electron Spectroscopy - Wiesing, Martin; de los Arcos de Pedro, Maria Teresa; Grundmeier, Guido (Advanced Materials Interfaces)

Electric potential screening on metal targets submitted to reactive sputtering - Corbella, Carles; Marcak, Adrian; von Keudell, Achim; de los Arcos de Pedro, Maria Teresa (Journal of Vacuum Science & Technology A: Vacuum, Surfaces, and Films)

Nitridische und oxinitridische HPPMS-Beschichtungen für den Einsatz in der Kunststoffverarbeitung (Teil 1) - Bobzin, Kirsten; Grundmeier, Guido; Brögelmann, Tobias; de los Arcos de Pedro, Maria Teresa; Wiesing, Martin; Kruppe, Nathan C. (Vakuum in Forschung und Praxis)